2015
DOI: 10.1002/pssc.201400322
|View full text |Cite
|
Sign up to set email alerts
|

Electrical performance of the InGaP solar cell irradiated with low energy electron beams

Abstract: The investigation of the radiation degradation characteristics of InGaP space solar cells is important. In order to understand the mechanism of the degradation by radiation the samples of the InGaP solar cell were irradiated in vacuum and at ambient temperature with electron beams from a Cockcroft‐Walton type accelerator at Osaka Prefecture University. The threshold energies for recoil were obtained by theoretical calculation. The energies and the fluences of the electron beams were from 60 to 400 keV and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In studies focusing on the DDD model, the effect of a change in the value of E d on the accuracy of degradation prediction has been frequently confirmed via irradiation tests, using high-energy electrons (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The E d of phosphorus is reported to be approximately 9 eV in the InGaP solar cells.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In studies focusing on the DDD model, the effect of a change in the value of E d on the accuracy of degradation prediction has been frequently confirmed via irradiation tests, using high-energy electrons (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The E d of phosphorus is reported to be approximately 9 eV in the InGaP solar cells.…”
Section: Introductionmentioning
confidence: 98%
“…5) However, in our previous studies, it was observed that electrons at 60 keV generate radiation-induced defects resulting from the recoil of phosphorus atoms and thus cause the degradation of InGaP solar cells. [6][7][8] This unexpected degradation is probably caused by the incorrect value of displacement threshold energy (E d ) in NIEL.…”
Section: Introductionmentioning
confidence: 99%
“…The InGaP SJ solar cells were the same as those used in our previous studies. 16,17) The dimensions and physical properties of the InGaP and GaAs SJ solar cells are indicated in Table I. These samples did not have a cover glass or an anti-reflective coating on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…These E th values well agree with those in the NIEL. 17,20) In this work, an electron energy of 70 keV, sufficiently lower than E th , is chosen to study the effects of irradiation on the InGaP and GaAs solar cells.…”
Section: Calculation Of Energy Of Electrons At Damage Thresholdmentioning
confidence: 99%
See 1 more Smart Citation